Organizational Citizenship Behavior on Public Organizational Performance - Mahfudz Mahfudz; I Made Sukresna; Rio Dhani Laksana; Intan Shaferi (Journal of International Conference Proceedings (JICP), 2019)
The research aims to examine the behaviors and perceptions of public employees regarding organizational performance through their voluntary contributions to the functioning of their organization. OCB can mediate the relationship between subjective constructs of organizational performance and the perceptions of employees regarding their leaders as well as their motivation to serve in the public sector. The purpose of this study is mapping Organizational Citizenship Behavior Model on Public Organizational Performance. The research was conducted in 3 City Sector public area, The population in this research was all employees at public sector organization in 3 Regency City in Central Java: Semarang, Purworejo and Purwokerto. The sample selection was conducted through purposive sampling method. The sample sin this research were civil servants of the financial section in SKPD with the number of 300 respondents. The data used in this study were primary data through the questionnaires.